PENGARUH PENERAPAN E-SAMSAT DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Kurniawan, Miko Katon; Hidayat, Vinny Stephanie (COMPETITIVE, 2024)
The aim of this research is to examine the application of e-Samsat and tax sanctions in influencing motor vehicle taxpayer compliance with the Cimahi Samsat. For this reason, a sample of 70 people was selected. Data was obtained through distributing questionnaires. Multiple regression analysis was the technique applied for data analysis. Verified test results show that the implementation of e-Samsat has no effect on taxpayer compliance and tax sanctions have a positive and significant effect on tax compliance.